How do you simplify (3/4)abs4 + (-3) – (-1)?

2 Answers
Jul 7, 2015

(3/4)abs(4)+(-3)-(-1) = 1

Explanation:

Evaluate the function abs first
Since abs(4) = 4
The expression becomes
color(white)("XXXX")(3/4)(4)+(-3)-(-1)

Evaluate the multiplication next
Since (3/4)(4) = 3
The expression becomes
color(white)("XXXX")3+(-3)-(-1)

Evaluate addition and subtraction starting from the left
Since 3+(-3) = 0
The expression becomes
color(white)("XXXX")0-(-1)

Perform the final subtraction
Since -(-1) = +1
The expression reduces to
color(white)("XXXX")1

Jul 11, 2015

(3/4)*|4|+(-3)-(-1)=1

Explanation:

1.) First, let's look at "the absolute value" of 4

Recall that "the absolute value" of something is something and "the absolute value" of (negative)something is something:

|something| = something
|-something| = something

So, |4| = 4

2.) So, the (3/4)*|4| part becomes (3/4)*4 which is 3

(Those 4's cancel out)

3.) Now, we are left with:

3+(-3)-(-1)

The +(-3) is just -3

because (plus) a (negative)something is (negative)something:

+(-something) = -something

and the -(-1) is just +1

because (minus) a (negative)something is (positive)something:

-(-something) = +something

4.) So, now we have:

3-3+1

3-3 is 0 and we are then left with 1

So, 1 is our answer (our simplified junk from above)